Pengaruh Peran Event Organizer Terhadap Peningkatan Sumber Daya Manusia (SDM) Kota Surakarta - Iqbal Rizky Nur Istanto; Maulidyah Indira Hasmarani (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
Event Organizers (EO) have an important role  in  the  creative  industry,  especially  in improving the quality of human resources (HR) through various activities involving event planning, management and execution. This research aims to analyze the influence of the role of Event Organizer on improving human resources in the city of Surakarta. The research method used is a quantitative approach by collecting data through surveys of workers involved in the event industry as well as interviews with event organizers. The research results show that involvement in the events industry contributes to improving workers' communication, managerial and problem-solving skills. Apart from that, Event Organizers also play a role in opening up job opportunities and building wider professional networks. With training and direct experience in organizing events, the quality of human resources in the city of Surakarta has increased significantly. This research concludes that the role of the Event Organizer is very influential in developing individual competence and workforce competitiveness in the creative industry sector.